2010
DOI: 10.3136/fstr.16.93
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Superheated Steam Treatment on Enzymes Related to Lipid Oxidation of Brown Rice

Abstract: When brown rice is preserved for a long period of time, a stale flavor (komai-shu) develops as a result of lipid oxidation by enzymes. In order to inactivate the enzymes, brown rice was treated with superheated steam. Superheated steam treatment for about 1 min, at all temperatures, caused a decrease in the enzymatic activity related lipid oxidation. On the other hand, the degree of starch damage did not increase during superheated steam treatment below 150℃. These results show that superheated steam treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Therefore, low temperature and short time SS treatments (110 C, 3.5 min and 120 C, 2.5 min) were enough to suppress the peroxidase activity in LMR and the treatment time required to inactivate peroxidase in LMR was shorter than that of synthermal HA. These results are in agreement with that of Satou et al (2010), who observed that a short time (1 min) SS treatment at low temperature (125 C) was enough to inactivate lipolytic enzymes of brown rice. Head et al (2010) also reported that low temperature SS (110e160 C) was effective to inactivate peroxidase in oat groats, and the SS processed oat groats has good storage stability (Head et al, 2010(Head et al, , 2011.…”
Section: Resultssupporting
confidence: 95%
See 3 more Smart Citations
“…Therefore, low temperature and short time SS treatments (110 C, 3.5 min and 120 C, 2.5 min) were enough to suppress the peroxidase activity in LMR and the treatment time required to inactivate peroxidase in LMR was shorter than that of synthermal HA. These results are in agreement with that of Satou et al (2010), who observed that a short time (1 min) SS treatment at low temperature (125 C) was enough to inactivate lipolytic enzymes of brown rice. Head et al (2010) also reported that low temperature SS (110e160 C) was effective to inactivate peroxidase in oat groats, and the SS processed oat groats has good storage stability (Head et al, 2010(Head et al, , 2011.…”
Section: Resultssupporting
confidence: 95%
“…In contrast, the moisture content in SS treated LMR was increased slightly at the initial stage, and then decreased at rates much lower than those of synthermal HA treated LMR. Satou et al (2010) also found a slight increase in moisture content at the initial stage when brown rice was subjected to low temperature SS (125 and 150 C). This phenomenon was probably due to the high relative humidity of superheated steam reducing the drying effect.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The extensive literature survey carried out in this work indicated that the majority of these reports are on drying of food products (Li et al, 1999;Tang et al, 2000;Tang and Cenkowski, 2000;Caixeta et al, 2002;Markowski et al, 2003;Huang et al, 2004;Nathakaranakule et al, 2007;Nimmol et al, 2007;Suvarnakuta et al, 2011). The other applications reported are enzyme inactivation (Pronyk et al, 2005;Sotome et al, 2009;Satou et al, 2010;Head et al, 2011), decontamination Cenkowski et al, 2007;Kondijoyan and Portanguen, 2008) and microbial load reduction (Shull and Ernst, 1962;Nygaard and Hostmark, 2008;Head et al, 2008) of foods. Recently, process improvisations such as superheated steam processing under low pressure, fluidized bed heating, in combination with infrared radiation and with water droplets have been attempted by researchers to improve product quality and energy efficiency.…”
Section: Introductionmentioning
confidence: 95%